PERKEMBANGAN TEKNOLOGI KOMUNIKASI DALAM ERA JURNALISTIK MODERN - Hadi, Ido Prijana (Scriptura, 2009)
Internet technology has made communication much easier and less expensive. It has attracted many people and has penetrated into people’s daily lives. The mass media also have accepted the internet. Almost all forms of traditional media, such as radio, television, and newspaper have extended their work into this new field. The internet and the world wide web have both significantly influenced modern journalism. Many television, radio broadcasting stations, and newspapers in Indonesia operate their sites using internet technology. Internet brings a technical communication revolution, a fundamental change takes place in the structure of connections, artificial memories and the reproduction of their content. In online media allows readers to enjoy browsing their product and service of contents, such as news feed, podcasts, deskstop alert, news on mobile phones, PDA and others mobile devices. Online media offer not only text but also digital images, audio file, and moving images (video). The interactive features of the internet seemingly imply that online media have more advantages than traditional media forms. So, the internet have dramatically evolved become new media with characteristic multimedia, hypertext, interactivity, archives, and virtuality. The most important structural new media characteristic is the integration of telecommunications, data communications and mass communication in a single medium. It is the process of convergence.